Abstracts from the 2016 Research and Thesis Poster Session of the 51st Annual American Dance Therapy Association Conference. - Tantia, Jennifer; Fontanesi, Cecilia (American Journal of Dance Therapy, 2017)
The Research and Practice Committee of the American Dance Therapy Association (ADTA) has sponsored the research poster session at each annual conference for the past 21 years. The studies represented in the current abstracts from the 2016 Research and Thesis Poster Session of the 51st Annual ADTA conference feature a wide range of scholarly works and thesis projects in current dance/movement therapy trends. The following 22 studies have been selected for their quality and contributions to dance/movement therapy research.